Optical Detection of Glucose Using 3D-Printed Microfluidic Platform. BIOS2016 Gothenburg - Tothill, Alexander M. (Cranfield University, 2016)
Poster and data presented at Biosensors 2016 Conference Gothenburg Sweden.
Keywords: BIOS 2016 A M Tothill'; 'P2.006'; 'Microfluidic Device'; 'Glucose Assay'; '3D-Printing'; 'Medical Devices'